Shikonin suppresses proliferation of osteosarcoma cells by inducing ferroptosis through promoting Nrf2 ubiquitination and inhibiting the xCT/GPX4 regulatory axis - Huang, Rui; Chu, Dawei; Shi, Jiandang; Xu, Ruiqing; Wang, Kun (Frontiers in Pharmacology, 2024)
Osteosarcomas (OS) is a prevalent primary malignant bone tumor which lacks effective therapeutic interventions. Ferroptosis is a new form of programmed cell death characterized by irondependent accumulation of lethal lipid oxidation, which provides a potential alternative intervene for the OS treatment. Shikonin is the major bioactive component extracted from the roots of lithospermum erythrorhizon which is also known as "Zicao" in traditional Chinese medicine, has been proved to have exhibits remarkable anti-tumor properties in several cancers. However, whether ferroptosis participated in the shikonin mediated anti-OS activity still remains to be clarified. Herein, we provide evidence that shikonin possesses the capability to induce the ferroptosis, and elucidate the underlying mechanisms in the treatment of OS. In the present study, it was found that shikonin significantly suppressed OS cells proliferation and blocked the cell cycle progression in vitro. Subsequent results revealed that shikonin could trigger ferroptosis in OS cells by promoting the Fe 2+ accumulation, reactive oxygen species and lipid peroxidation formation, malondialdehyde production and mitochondrial damage. Further study showed that the effects of OS cell proliferation and death caused by shikonin could be successfully reversed by ferroptosis inhibitor ferrostatin-1, indicating that ferroptosis participated in the shikonin mediated anti-OS activity. Mechanistically, shikonin physically interacted with Nrf2, a critical regulator of ferroptosis, and influenced Nrf2 stability via inducing ubiquitin degradation, which suppressed the expression of Nrf2 downstream targets xCT and GPX4, and led to stimulating ferroptosis. Collectively, our findings indicated that shikonin induced OS cells ferroptosis through Nrf2/xCT/GPX4 regulatory axis, which might shed light on exploiting shikonin as a promising candidate for the future OS therapy.